Zdravotní stav a patogeny v experimentální výsadbě meruněk: Vývoj v čase - Martina Rejlová (VÝZKUMNÝ A ŠLECHTITELSKÝ ÚSTAV OVOCNÁŘSKÝ HOLOVOUSY s.r.o., 2021)
A significant dieback of apricots first years after planting, known as apoplexy of apricots, represents an important problem for growers. Studies are being conducted to identify causes of this phenomenon to prevent massive withering in apricot orchards. Between 2018 and 2021, health status of an experimental apricot orchard was monitored, in which nearly 10 % of trees died two-to-four years before 2018. Within the next three years, samples were collected three times (August 2018, December 2019, and May 2021) to study prevalence of pathogens in time. Sprout samples were PCR-analyzed for the presence of the following pathogens: ˈCandidatus Phytoplasma prunorumˈ, Pseudomonas syringae, and Cytospora spp. Our results showed an increase in prevalence of ˈCa. P. prunorumˈ in symptomatic trees (from slightly less than 40 % to nearly 60 %), while in asymptomatic trees the prevalence remains about the same (20 % – 26.4 %). Prevalence of Cytospora spp. was also considerably increased in older trees – it was detected in more than 25 % of apricots five to seven years of age. The presence of P. syringae was influenced by weather and sampling date, and it was not possible to assess its role in apricot apoplexy. Thus, ˈCandidatus Phytoplasma prunorumˈ and Cytospora fungi are likely two main players that adversely affect health status of apricot orchards, resulting in pre-mature dying of infected trees.